2018
DOI: 10.1016/j.yhbeh.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory behavior is linked to stress physiology and social network centrality in free-living house finches (Haemorhous mexicanus)

Abstract: Animal personality has been linked to individual variation in both stress physiology and social behaviors, but few studies have simultaneously examined covariation between personality traits, stress hormone levels, and behaviors in free-living animals. We investigated relationships between exploratory behavior (one aspect of animal personality), stress physiology, and social and foraging behaviors in wild house finches (Haemorhous mexicanus). We conducted novel environment assays after collecting samples of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 74 publications
(121 reference statements)
1
16
0
Order By: Relevance
“…This pattern has previously been observed in Eastern grey squirrels ( Sciurus carolinensis ) (Santicchia et al 2019). Exploratory behaviour is known to predict foraging style (Verbeek et al 1994; Aplin et al 2014) but to which extent is not fully understood (Moyers et al 2018). Ixodes ricinus (the most common tick infesting vertebrates in Europe (Hillyard 1996)) quests for hosts vertically up to 1.5m but with decreasing abundance with increasing distance from the ground (Mejlon and Jaenson 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern has previously been observed in Eastern grey squirrels ( Sciurus carolinensis ) (Santicchia et al 2019). Exploratory behaviour is known to predict foraging style (Verbeek et al 1994; Aplin et al 2014) but to which extent is not fully understood (Moyers et al 2018). Ixodes ricinus (the most common tick infesting vertebrates in Europe (Hillyard 1996)) quests for hosts vertically up to 1.5m but with decreasing abundance with increasing distance from the ground (Mejlon and Jaenson 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The Elo-rating is a rating-based method originally proposed for ranking chess players and subsequently applied to many animal behavioral studies (e.g., [ 17 , 18 , 19 , 20 ]). It is calculated as an individual score that updates sequentially after every dyadic interaction involving the individual themselves.…”
Section: Methodsmentioning
confidence: 99%
“…In one example, a study of juvenile cavies (Cavia aperea) found basal metabolic rates seemed to underlie an animal's propensity to explore habitats and likely facilitated finding scarce resources (Guenther et al 2014). Considering other motivations, it was shown in highly social, wild house finches (Haemorhous mexicanus) that reactive individuals were more flexible and 'explorative' in their behavior because they had the necessary energy to seek out intraspecific interactions in unfamiliar habitats (Moyers et al 2018), although these studies used glucocorticoids to infer energetic capabilities. Similarly, here, thyroid and body size differences may underlie behavioral and social motivations for GSL pups to locomote more and interact with conspecifics in greater portions of their habitat.…”
Section: Socio-ecological Statesmentioning
confidence: 99%